Application of convolutional neural networks in the intelligence security system subsystem - V. S. Demeshko; A. I. Фёдоров (Системный анализ и прикладная информатика)
The article proposes the structure of an integrated security system for areal facilities. The main subsystems included in its composition are considered. The tasks of the intelligence subsystem for detecting and recognizing ground-based objects of observation in a complex phono-target environment are defined.The task of detecting an object of observation was solved on the basis of a previously proposed algorithm. The disadvantage of this algorithm was the presence of false positives from a flickering complex phono-target environment. To eliminate this drawback, it is proposed to apply a classifier based on the convolutional neural network, which distributes the selected objects to specific classes.The analysis and experimental studies to evaluate the accuracy of recognition of ground objects by convolutional architectures such as VGG-16, VGG-19, Inception v3, ResNet-50, MobileNet. Training and verification of the recognition quality of architecture data was carried out on an experimentally created data set with a human image on a contrasting background and at different ranges. The results obtained indicate the possibility of using a convolutional neural network in the security system and its ability to work in real time.